Comparative Anatomy of the Right and Left Internal Jugular Veins: Implications for Optimal Central Venous Catheter Placement - Teeratakulpisarn, Panu; Tanmit , Parichat; Tiyanuchit , Kritthee; Angkasith, Phati; Wongkonkitsin, Narongchai; Prasertcharoensuk, Supatcha; Thanapaisal, Chaiyut (Journal of the Nephrology Society of Thailand, 2025)
Background: Central venous catheters are essential for dialysis, with the internal jugular vein (IJV) being the preferred access site. Recognizing anatomical variations of the IJV is crucial to avoid accidental arterial puncture. This study aims to describe anatomical variations of the right and left IJVs. Methods: We retrospectively reviewed neck CT scans from 123 patients who underwent imaging at our hospital between January 1, 2015, and December 31, 2019. We recorded the bilateral IJV diameter, depth from the skin, distance to the common carotid artery (CCA), and the IJV’s positional relationship to the CCA. The IJV’s position relative to the CCA was classified as lateral, anterior, anterolateral, medial, or posterior, based on its location at the level of the cricoid cartilage. Results: Most IJVs (90.24%) were positioned lateral to the CCA, with the left side demonstrating greater anatomical variation. The left IJV overlapped the CCA more frequently than the right in the anterolateral position, and only left IJVs were found in the anterior position. Right IJVs were larger in 85.4% of patients, with a significantly greater mean diameter (16.04±3.51 mm vs. 12.57±3.30 mm, p<0.001) and were more superficial (13.06±3.46 mm vs.14.28±3.26 mm, p <0.001) compared to the left. Conclusions: Due to less anatomical variability and a more favorable puncture site, the right IJV is generally more suitable for vascular access than the left.